Digital dilemma of muslim gen z filters facts, role of Islamic Education mental health - Karnefa, Sakila; Yudelnilastia, Yudelnilastia; Agustin, Widia; Febriany, Fina (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The phenomenon of virtual reality has become inseparable from the daily lives of Indonesian Muslim Gen Z, particularly through social media platforms such as TikTok. Excessive exposure to algorithm-driven content and visual filters significantly impacts mental health, including identity disturbance, anxiety, and social pressure. This study aims to explore how the construction of virtual reality on digital platforms affects the mental health of Muslim Gen Z and how Islamic values serve as a foundation for psychological resilience. Using a qualitative descriptive approach and literature study, this work examines empirical data from 2025, TikTok content trends, and ethical perspectives in Islamic teachings. The findings show that virtual reality does not fully represent real life and creates pressure regarding ideal physical appearance, lifestyle, and achievements. In this context, faith, self-awareness, and Islamic digital literacy become essential pillars in maintaining the mental well-being of Muslim Gen Z. This study is expected to serve as a strategic reference for fostering a healthier and more ethical media culture.